THE EDUCATIONAL THOUGHTS OF TGKH. MUHAMMAD ZAINUDDIN ABDUL MADJID IN THE WILLFUL REFLECTIONS OF NEW EXPERIENCES - Nasri, Ulyan; Atsani, Lalu Gede Muhammad Zainuddin; Fahrurrozi; Thohri, Muhammad (Universitas Islam Negeri Mataram, 2023)
This research aims to analyze the Islamic educational thoughts contained in the contemplative will of TGKH. Muhammad Zainuddin Abdul Madjid's new experiential period. The research method employed is literature analysis with a qualitative approach. Data were collected through literature studies and documentation related to the contemplative will. Data analysis was conducted by detailing the Islamic educational thoughts expressed in the will. The results of the research indicate that TGKH. Muhammad Zainuddin Abdul Madjid emphasizes the importance of Islamic education in shaping individual character, morality, and societal life. His thoughts also reflect the role of education in addressing the challenges of the times and fostering harmony between religion and science. The data analysis method involves identifying key concepts, interpreting meanings, and synthesizing the Islamic educational thoughts of TGKH. Muhammad Zainuddin Abdul Madjid. The implications of this research provide a deeper understanding of the values of Islamic education contained in the contemplative will, serving as a foundation for the development of curricula and practices in Islamic education that are more relevant to contemporary needs. In conclusion, the Islamic educational thoughts of TGKH. Muhammad Zainuddin Abdul Madjid in the contemplative will of the new experiential period contribute valuable insights to the development of holistic Islamic education in line with the demands of the times.